Endometrial pathologies in clinical follow-up of patients with hormone receptor-positive/negative breast cancer: Clinical experience in endometrial pathologies at a tertiary center - Kurt, Sefa; Ozmen, Samican; Yavuz, Onur; Ilgen, Orkun; Ulukus, Emine Cagnur (Journal of Surgery and Medicine, 2023)
Background/Aim: Breast cancer is the leading cause of cancer-related fatalities in women. Tamoxifen, a selective estrogen receptor modulator (SERM), is frequently employed for chemoprevention in hormone receptor (HR)-positive breast cancer patients due to its anti-estrogenic impact on breast tissue. Nevertheless, tamoxifen exhibits agonistic effects on the endometrium, particularly in postmenopausal women. This study aims to assess gynecological issues and endometrial pathologies that emerge during the treatment and follow-up phases of women diagnosed with HR-positive/negative breast cancer. Methods: This cohort study involved a data review from 857 breast cancer patients diagnosed over a decade at a tertiary center. Histopathological endometrial findings were evaluated for 166 patients who underwent gynecological consultations before breast cancer treatment with normal examination results and underwent invasive assessments due to gynecological symptoms that arose during treatment and follow-up. The study encompassed cases culminating in total abdominal hysterectomy and bilateral salpingo-oophorectomy (TAH+BSO). Results: The study analyzed 166 cases meeting the inclusion criteria. The mean age at breast cancer diagnosis was 48 years with a standard deviation of 8.4 years, and the average follow-up duration was 4.1 (3.8) years. The predominant histopathological type was invasive ductal carcinoma (75.3%). Of the cases, 68.6% occurred during premenopausal and 31.4% during postmenopause. HR positivity was identified in 136 cases (81.9%), while 30 (18.1%) exhibited negative HR status. Among HR-positive cases, 113 (83.0%) received tamoxifen treatment, while 23 (17.0%) were treated with letrozole. Common clinical findings during and after treatment encompassed increased endometrial thickness (ET) and abnormal uterine bleeding (AUB). Histopathological evaluation of invasive procedures prompted by increased ET indicated the following frequent endometrial findings: proliferative endometrium (33.1%), endometrial polyp (20.5%), and endometrial hyperplasia (EH) without atypia (9%). The histopathological outcomes of invasive procedures prompted by AUB included atrophic endometrium (11.4%), proliferative endometrium (3.6%), and endometrial cancer (1.8%). Among the endometrial malignancies, three occurred in the premenopausal phase and four in the postmenopausal phase. Notably, three of the seven endometrial malignancies were observed in the tamoxifen hormone therapy group, all HR-positive. Four cases were from the non-tamoxifen hormone therapy group with negative HR status. Conclusion: Globally, breast cancer ranks as the most prevalent malignancy in women. Tamoxifen, a frequently utilized adjuvant therapy post breast cancer surgery, can exert diverse effects on gynecological organs, encompassing benign pathologies like increased ET and malignant pathologies like uterine neoplasia. There is a rising suspicion that etiopathogenetic factors contributing to breast cancer progression might also precipitate uterine cancer, irrespective of tamoxifen use. Vigilant patient monitoring is paramount for detecting uterine neoplasia and other gynecological pathologies.